Strategic Leadership to Prevent Corruption in Indonesia - Sarjito, Aris (Advances in Social Sciences Research Journal, 2020)
In the General Explanation of the 2002 KPK Law, it states: Increased corruption unhindered creates disasters, not only for the national economy, but also for national and state life in general. Extensive and systematic corruption is also a violation of the social and economic rights of the community and, therefore, corruption can no longer be classified as an ordinary crime, but rather as an extraordinary crime. By any standard, Indonesia's corruption level is high. There are indications that since the fall of Suharto, overall corruption has actually increased. Regional autonomy is generally blamed for dispersing power to regional officials, many of whom are expected to exploit their offices for personal gain. This study uses a qualitative analysis approach that aims to analyze strategic leadership to prevent corruption in Indonesia, using Hughes's strategic leadership theory as an analysis tool. The results of this study are: (1) good governance requires transparency in the management of regional development using the budget originating from the APBN (state budget) and APBD (local budget); (2) strategic leaders always encourage the creation of clean bureaucracy; Organizational principles are encouraged to prohibit illegal actions against the internal environment and, in particular, external organizations will have an impact in the long term and grow the organization to be healthier; and (3) a strategic leader in running an organization must hold fast to the principle of legality and anti-corruption. Keywords: corruption, strategic leadership.